TPE (thermoplastic elastomer) material as well as preparation method and application thereof

By using components such as polyether block amide and nylon in TPE materials, combined with maleic anhydride graft polymer and glycidyl methacrylate graft olefin copolymer elastomer, the poor polarity and difficulty of bonding of TPE materials on nylon are solved, and efficient glue-in and anti-static properties are achieved.

CN119529549AActive Publication Date: 2025-02-28KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411714212.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to glue permanent antistatic TPE materials on nylon materials, mainly due to poor material polarity and antistatic properties, which lead to difficulty in bonding.

Method used

Polyether block amide is used as an antistatic agent, and nylon, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene propylene teremer and glycidyl methacrylate grafted olefin copolymer elastomer are added to improve the adhesion and antistatic properties of the material.

Benefits of technology

It achieves good adhesive properties, strong bonding and high antistatic properties of TPE materials on nylon, while improving the tensile strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156523550000011
    Figure BDA0005156523550000011
  • Figure BDA0005156523550000071
    Figure BDA0005156523550000071
  • Figure BDA0005156523550000081
    Figure BDA0005156523550000081
Patent Text Reader

Abstract

The invention discloses a TPE (thermoplastic elastomer) material as well as a preparation method and application thereof, and belongs to the technical field of thermoplastic elastomer polymer materials. According to the TPE material, polyether block amide is used as an antistatic agent; the nylon, the maleic anhydride grafted polypropylene, the maleic anhydride grafted ethylene propylene diene monomer, the maleic anhydride grafted hydrogenated styrene elastomer and the polyacrylamide are added, so that the strength of the material and the bonding performance with the PA are improved. The TPE material has good nylon encapsulation performance, antistatic performance and mechanical performance, and is suitable for being applied to encapsulation of battery pack shells, encapsulation of explosion-proof tool shells and encapsulation of vehicle parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermoplastic elastomer polymer materials, and in particular to a TPE material and a preparation method and application thereof. Background Art

[0002] Thermoplastic elastomer (TPE for short) has both the processing properties of thermoplastics and is easy to process, and the physical properties of vulcanized rubber, such as high elasticity, high strength, and high resilience. An important application of TPE is to be used as a coating material (i.e., encapsulation), that is, encapsulating TPE soft rubber materials on other materials. However, it is difficult to encapsulate permanent antistatic TPE materials on nylon (i.e., PA, polyamide) materials. On the one hand, this is because PA has a strong polarity, while permanent antistatic TPE materials are mainly composed of SEBS, white oil, PP, POE and other components, and have weak polarity, and the polarity of the two differs greatly; on the other hand, it is because the permanent antistatic TPE material itself has antistatic properties, making it difficult to bond.

[0003] Therefore, it is necessary to develop a permanent antistatic TPE material with good nylon encapsulation performance and mechanical properties. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of this application is to provide a TPE material and its preparation method and application, aiming to make the TPE material have good antistatic properties, nylon encapsulation properties and mechanical properties.

[0005] In order to achieve the above objectives, in a first aspect, the present application provides a TPE material comprising the following components in parts by weight:

[0006]

[0007] Polyether block amide has ion channels, which can give TPE materials antistatic properties. The amide group in nylon has high strength, which can greatly improve the strength and toughness of the material. At the same time, it belongs to the same material as the material nylon to be coated, which can significantly improve the encapsulation performance of the material on PA. The maleic anhydride in maleic anhydride grafted polypropylene, maleic anhydride grafted EPDM rubber and maleic anhydride grafted hydrogenated styrene elastomer can react with the amide group of nylon, which is beneficial to improve the bonding performance of the material on nylon. Among them, the addition of maleic anhydride grafted polypropylene can also adjust the hardness of the material to avoid the material being too hard; the addition of maleic anhydride grafted hydrogenated styrene elastomer increases the content of hydrogenated styrene elastomer in the material, which increases the overall tensile strength; compared with maleic anhydride grafted polypropylene and maleic anhydride grafted hydrogenated styrene elastomer, the maleic anhydride in maleic anhydride grafted EPDM rubber is easier to play a role and is more conducive to improving the bonding strength between the material and nylon. The addition of glycidyl methacrylate grafted olefin copolymer elastomer can, on the one hand, promote the compatibility of polyether block amide and hydrogenated styrene elastomer, establish better ion channels, and improve antistatic properties; on the other hand, it can increase the activity of maleic anhydride grafted material and promote the bonding of the material with nylon. Polyacrylamide is beneficial to improve the compatibility of nylon with other components in the material and enhance the strength of the material.

[0008] Under the joint action of the above-mentioned specific contents of each component, the TPE material can not only be well encapsulated on PA with strong adhesion, but also has good antistatic properties and good mechanical properties, such as high tensile strength.

[0009] The hydrogenated styrene elastomer is 8 to 32 parts by weight, such as 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 32 parts by weight or a range formed by any two of the above values.

[0010] The mineral oil is 20 to 60 parts by weight, such as 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight or a range formed by any two of the above values.

[0011] The nylon is 1 to 15 parts by weight, such as 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight or a range formed by any two of the above values.

[0012] The glycidyl methacrylate grafted olefin copolymer elastomer is 1 to 10 parts by weight, such as 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight or a range formed by any two of the above values.

[0013] The maleic anhydride grafted polypropylene is 1 to 20 parts by weight, such as 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight or a range formed by any two of the above values.

[0014] The maleic anhydride grafted EPDM rubber is 3 to 20 parts by weight, such as 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight or a range formed by any two of the above values.

[0015] The maleic anhydride grafted hydrogenated styrene elastomer is 1 to 20 parts by weight, such as 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 17 parts by weight, 20 parts by weight or a range formed by any two of the above values.

[0016] The polyether block amide is 8 to 12 parts by weight, such as 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 10.5 parts by weight, 11 parts by weight, 11.5 parts by weight, 12 parts by weight or a range formed by any two of the above values. Preferably, the polyether block amide is 8.8 to 11.2 parts by weight to better balance the adhesion and antistatic properties of the material on PA.

[0017] The polyacrylamide is 1 to 5 parts by weight, such as 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, 5 parts by weight or a range formed by any two of the above values.

[0018] The filler is 5 to 50 parts by weight, such as 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight or a range formed by any two of the above values.

[0019] Preferably, the weight ratio of the nylon to the polyacrylamide is (0.5-10):1, such as 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 10:1 or a range formed by any two of the above values. More preferably, the weight ratio of the nylon to the polyacrylamide is (1.3-3):1.

[0020] When the weight ratio of the nylon to the polyacrylamide is in the range of (0.5-10):1, especially in the range of (1.3-3):1, the nylon encapsulation performance and antistatic performance of the material are better.

[0021] Preferably, the hydrogenated styrene-based elastomer includes at least one of a hydrogenated styrene-butadiene block copolymer and a hydrogenated styrene-isoprene block copolymer.

[0022] Preferably, the rubber content of the hydrogenated styrene elastomer is 60wt.% to 80wt.%, and the styrene content is 20wt.% to 40wt.%. For example, the rubber content of the hydrogenated styrene elastomer is 60wt.%, 62wt.%, 64wt.%, 66wt.%, 68wt.%, 70wt.%, 72wt.%, 74wt.%, 76wt.%, 78wt.%, 80wt.% or a range formed by any two of the above values; the styrene content is 20wt.%, 22wt.%, 24wt.%, 26wt.%, 28wt.%, 30wt.%, 32wt.%, 34wt.%, 36wt.%, 38wt.%, 40wt.% or a range formed by any two of the above values. The rubber content and styrene content in the hydrogenated styrene elastomer can be obtained by nuclear magnetic resonance hydrogen spectrum detection.

[0023] Preferably, the relative viscosity of the hydrogenated styrene elastomer in a toluene solution at 25° C. with a content of 10 wt % is 1500-3000. For example, the relative viscosity of the hydrogenated styrene elastomer in a toluene solution at 25° C. with a content of 10 wt % is 1500, 1700, 2000, 2200, 2500, 2800, 3000 or a range formed by any two of the above values. The relative viscosity of the hydrogenated styrene elastomer is measured by a kinematic viscosity test method.

[0024] Preferably, the mineral oil includes at least one of silicone oil, paraffin oil, cycloparaffin oil and aromatic hydrocarbon oil.

[0025] Preferably, the viscosity of the nylon is 90-180cm 3 / g. For example, the viscosity of the nylon is 90cm 3 / g、100cm 3 / g, 110cm 3 / g, 120cm 3 / g, 130cm 3 / g, 140cm 3 / g, 150cm 3 / g, 160cm 3 / g, 170cm 3 / g, 180cm 3 / g or a range formed by any two of the above values. The viscosity of the nylon is measured according to ISO 307:2019.

[0026] Preferably, the nylon comprises nylon 6.

[0027] Preferably, the grafting rate of the glycidyl methacrylate grafted olefin copolymer elastomer in the glycidyl methacrylate grafted olefin copolymer elastomer is 0.5wt.% to 3wt.%. For example, the grafting rate of the glycidyl methacrylate grafted olefin copolymer elastomer in the glycidyl methacrylate grafted olefin copolymer elastomer is 0.5wt.%, 0.7wt.%, 1wt.%, 1.2wt.%, 1.4wt.%, 1.6wt.%, 1.8wt.%, 2wt.%, 2.2wt.%, 2.4wt.%, 2.6wt.%, 2.8wt.%, 3wt.% or a range formed by any two of the above values. The grafting rate can be measured by titration.

[0028] Preferably, the melt flow rate of the glycidyl methacrylate grafted olefin copolymer elastomer at 190°C and 2.16kg is 2.0 to 5.0 g / 10min. For example, the melt flow rate of the glycidyl methacrylate grafted olefin copolymer elastomer at 190°C and 2.16kg is 2.0 g / 10min, 2.5 g / 10min, 3.0 g / 10min, 3.5 g / 10min, 4.0 g / 10min, 4.5 g / 10min, 5.0 g / 10min or a range formed by any two of the above values. The melt flow rate is measured according to ASTM D1238-2010.

[0029] Preferably, the glycidyl methacrylate grafted olefin copolymer elastomer comprises glycidyl methacrylate grafted POE.

[0030] Preferably, the maleic anhydride grafted polypropylene includes at least one of maleic anhydride grafted homopolypropylene, maleic anhydride grafted copolymer polypropylene and maleic anhydride grafted random copolymer polypropylene.

[0031] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is ≥ 0.8 wt.%. For example, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.% or 1.5 wt.%, etc. The grafting rate can be measured by titration.

[0032] Preferably, the melt flow rate of the maleic anhydride grafted polypropylene at 190°C and 0.325kg is 5-30g / 10min. For example, the melt flow rate of the maleic anhydride grafted polypropylene at 190°C and 0.325kg is 5g / 10min, 7g / 10min, 10g / 10min, 12g / 10min, 15g / 10min, 17g / 10min, 20g / 10min, 22g / 10min, 25g / 10min, 27g / 10min, 30g / 10min or a range formed by any two of the above values. The melt flow rate is measured according to ASTMD1238-2010.

[0033] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted EPDM rubber is ≥ 0.8 wt.%. For example, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 0.8 wt.%, 0.9 wt.%, 1.0 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.% or 1.5 wt.%, etc. The grafting rate can be measured by titration.

[0034] Preferably, the melt flow rate of the maleic anhydride grafted EPDM rubber at 190°C and 2.16kg is 0.1 to 1.8 g / 10min. For example, the melt flow rate of the maleic anhydride grafted EPDM rubber at 190°C and 2.16kg is 0.1 g / 10min, 0.3 g / 10min, 0.5 g / 10min, 0.7 g / 10min, 1 g / 10min, 1.2 g / 10min, 1.5 g / 10min, 1.8 g / 10min or a range formed by any two of the above values. The melt flow rate is measured according to ASTM D1238-2010.

[0035] Preferably, the maleic anhydride grafted hydrogenated styrene-based elastomer includes at least one of a maleic anhydride grafted hydrogenated styrene-butadiene block copolymer and a maleic anhydride grafted hydrogenated styrene-isoprene block copolymer.

[0036] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted hydrogenated styrene elastomer is ≥ 1.7 wt.%. For example, the grafting rate of maleic anhydride in the maleic anhydride grafted polypropylene is 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.% or 2.5 wt.%, etc. The grafting rate can be measured by titration.

[0037] Preferably, the melt flow rate of the maleic anhydride grafted hydrogenated styrene elastomer at 230°C and 5kg is 5 to 40g / 10min. For example, the melt flow rate of the maleic anhydride grafted hydrogenated styrene elastomer at 230°C and 5kg is 5g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, 30g / 10min, 35g / 10min, 40g / 10min or a range formed by any two of the above values. The melt flow rate is measured according to ASTM D1238-2010.

[0038] Preferably, the weight ratio of styrene to rubber in the maleic anhydride grafted hydrogenated styrene elastomer is 2 / 8 to 4 / 6. For example, the weight ratio of styrene to rubber in the maleic anhydride grafted hydrogenated styrene elastomer is 2 / 8, 3 / 7, 4 / 6 or a range formed by any two of the above values. The weight ratio can be obtained by nuclear magnetic resonance hydrogen spectrum detection.

[0039] Preferably, the polyether block amide comprises polyamide-polyglycol, such as polyamide 12-polytetramethylene glycol.

[0040] Preferably, the polyether block amide has a melting point of 160-190° C. For example, the polyether block amide has a melting point of 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C. or a range formed by any two of the above values. The melting point is measured according to ISO 11357-1-2016.

[0041] Preferably, the weight average molecular weight of the polyacrylamide is 1 million to 8 million. For example, the weight average molecular weight of the polyacrylamide is 1 million, 2 million, 3 million, 4 million, 5 million, 6 million, 7 million, 8 million or a range formed by any two of the above values. The weight average molecular weight can be measured by gel permeation chromatography.

[0042] Preferably, the filler includes at least one of white carbon black, wollastonite, calcium carbonate, glass microspheres, talc, kaolin, diatomaceous earth, barium sulfate and mica. Preferably, the calcium carbonate is heavy calcium carbonate.

[0043] Preferably, the particle size of the filler is 100-4000 mesh. For example, the particle size of the filler is 100 mesh, 500 mesh, 1000 mesh, 1500 mesh, 2000 mesh, 2500 mesh, 3000 mesh, 3500 mesh, 4000 mesh or a range formed by any two of the above values. The particle size can be measured by a sieve method.

[0044] Preferably, the TPE material further comprises the following components in parts by weight: 0.1 to 2 parts of auxiliary agent.

[0045] Preferably, the auxiliary agent includes at least one of an antioxidant, a light stabilizer and a lubricant.

[0046] Preferably, the antioxidant includes at least one of 2,6-di-tert-butyl-4-methylphenol, antioxidant 1010, antioxidant 1076, antioxidant 1790, antioxidant 168 and antioxidant 626.

[0047] Preferably, the light stabilizer comprises a hindered amine light stabilizer and a triazine light stabilizer, and the weight ratio of the hindered amine light stabilizer to the triazine light stabilizer is (0.1-0.5):1.

[0048] Preferably, the hindered amine light stabilizer includes at least one of light stabilizer 622, light stabilizer 770, light stabilizer 944, light stabilizer 783, light stabilizer 791, light stabilizer 3853, light stabilizer 292 and light stabilizer 123; the triazine light stabilizer includes at least one of UV 329, UV-234, UV-236 and UV-2373.

[0049] Preferably, the lubricant includes at least one of vinyl bisstearamide, hydroxy fatty acid lubricant, erucic acid amide, zinc stearate, magnesium stearate and polyethylene wax.

[0050] Preferably, the mass fraction of the hydrogenated styrene elastomer in the TPE material is above 10%, such as 10%, 12%, 14%, 16%, 18%, 20%, or a range formed by any two of the above values.

[0051] The TPE material described in the present application may contain common additives such as color powder without impairing the effect of the present application.

[0052] In a second aspect, the present application provides a method for preparing the TPE material, comprising the following steps:

[0053] spraying mineral oil into the hydrogenated styrene elastomer while stirring to obtain a premix;

[0054] The premix is ​​mixed with other raw materials, melt-extruded, granulated, and dried to obtain a TPE material.

[0055] Preferably, the melt extrusion temperature is 170-250°C.

[0056] Preferably, melt extrusion is carried out in a twin-screw extruder, and the aspect ratio of the twin-screw extruder is above 36: 1. The aspect ratio of the twin-screw extruder can be selected as 36: 1, 40: 1, 42: 1, 45: 1, etc.

[0057] In a third aspect, the present application provides the application of the TPE material in the rubber coating of battery pack shells or explosion-proof tool shells, wherein the explosion-proof tool shells are, for example, explosion-proof shells of portable compressors.

[0058] In a fourth aspect, the present application provides a rubber-coated nylon product, which includes a nylon matrix and a coating material coated on the surface of the nylon matrix, and the coating material is the TPE material.

[0059] Compared with the prior art, the beneficial effects of this application are:

[0060] (1) The TPE material of the present application uses polyether block amide as an antistatic agent; nylon is added to improve its strength, toughness and adhesion performance on PA; maleic anhydride grafted polypropylene, maleic anhydride grafted EPDM rubber and maleic anhydride grafted hydrogenated styrene elastomer are added to improve the adhesion performance of the material on PA, adjust the hardness and improve the tensile strength; glycidyl methacrylate grafted olefin copolymer elastomer is added to promote the compatibility of polyether block amide and hydrogenated styrene elastomer, improve antistatic properties, and at the same time increase the activity of maleic anhydride grafts to promote the adhesion of the material to nylon.

[0061] (2) The TPE material of the present application can be well coated on PA, has strong adhesion, good appearance, no abnormal texture on the surface, good antistatic properties, and good mechanical properties, such as high tensile strength. It is suitable for use in battery pack shell coating, explosion-proof tool shell coating, and automotive parts coating. DETAILED DESCRIPTION

[0062] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0063] The raw materials used in the following examples and comparative examples are shown in Table 1, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.

[0064] Table 1

[0065]

[0066] Each of the following examples and comparative examples provides a TPE material, and the preparation methods of these materials are as follows:

[0067] spraying mineral oil into the hydrogenated styrene elastomer while stirring to obtain a premix;

[0068] The premix is ​​mixed with other raw materials, added into a twin-screw extruder for melt extrusion, granulated, and dried to obtain a TPE material, wherein the aspect ratio of the twin-screw extruder is 42:1, and the melt extrusion temperature is 170-250°C.

[0069] The formulations of these examples and comparative example TPE materials are shown in Tables 2 and 3.

[0070] Table 2

[0071]

[0072] Table 3

[0073]

[0074]

[0075] The following performance tests were performed on the above embodiments and comparative examples, and the test results are shown in Table 4.

[0076] Adhesion strength test method: According to the requirements of GB / T 7760-2003 standard, the TPE material is injected onto the nylon substrate strip on a specific mold using an injection molding machine (the nylon substrate strip material is a glass fiber reinforced PA6 composite material, composed of the following components by weight: 100 parts of PA6 (manufacturer model as above), 30 parts of glass fiber), the injection molding temperature is 235°C, and after being placed at 25°C for 24 hours, a 90° peel test is performed using a stretching machine to measure the bonding strength between the TPE material and the nylon substrate strip, and the bonding strength is divided into the following grades:

[0077] A: Can be peeled off easily, the peeling surface is smooth and has no residue;

[0078] B: There is resistance when peeling, and the residue on the peeling surface is less than 50%;

[0079] C: It is difficult to peel off the edges and corners, the residue on the peeling surface is 50% (excluding 50%)-99%, and the peeling force is large;

[0080] D: It is difficult to peel off the edges and corners. The TPE is broken and cannot be peeled off.

[0081] Tensile strength test method: According to ISO527-2012 standard test, after injection molding into a 2*100*100mm standard square plate, use a cutter to cut into 2-type specimens, place at 25℃ for 24 hours, and then test on a tensile machine. The molding cycle shall be based on the cycle of the injection molding tensile specimen.

[0082] Surface resistivity test method: After the sample is injection molded into a 2*100*100mm standard square plate, it is placed at 25℃ for 24 hours and then the surface resistivity is tested using a surface resistivity meter. For antistatic materials, the lower the surface resistivity, the better the antistatic performance; the larger the surface resistivity, the better the insulation performance. The surface resistivity of the object is ≥10 12 Ω is an insulator; greater than 10 5 Ω and less than or equal to 10 11 Ω is antistatic material.

[0083] Table 4

[0084]

[0085]

[0086] From the above data, it can be seen that the materials of each embodiment not only have good bonding performance with PA, but also have good mechanical properties and antistatic properties. For example, the bonding strength grade with PA is above C grade, the tensile strength is above 3.8MPa, and the surface resistivity is above 10 11 Below Ω, the comprehensive performance of the above three properties is good, and it is suitable for battery pack shell packaging, explosion-proof tool shell packaging and automotive parts packaging materials.

[0087] Compared with Example 1, Comparative Example 1 uses maleic anhydride grafted polyethylene instead of maleic anhydride grafted polypropylene. Due to the deviation in fluidity of maleic anhydride grafted polyethylene, it is not conducive to heat preservation and is not conducive to the reaction between maleic anhydride and nylon, resulting in deviation in the bonding performance of the material on PA.

[0088] Compared with Example 1, Comparative Example 2 did not add polyacrylamide and had a lower tensile strength.

[0089] Compared with Example 1, Comparative Examples 3 to 6 only added three of the glycidyl methacrylate grafted olefin copolymer elastomer, maleic anhydride grafted polypropylene, maleic anhydride grafted EPDM rubber and maleic anhydride grafted hydrogenated styrene elastomer, resulting in reduced adhesion, tensile strength and antistatic properties of the material on PA, indicating that these four compatibilizers synergistically improve the adhesion, tensile strength and antistatic properties of the material.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A TPE material, characterized in that: The composition comprises the following components in parts by weight:

2. The TPE material according to claim 1, characterized in that The weight ratio of the nylon to the polyacrylamide is (0.5-10):1; preferably, the weight ratio of the nylon to the polyacrylamide is (1.3-3):

1.

3. The TPE material according to claim 1, characterized in that The polyether block amide is 8.8 to 11.2 parts by weight.

4. The TPE material according to claim 1, characterized in that Satisfy at least one of the following conditions (1) to (6): (1) The hydrogenated styrene elastomer comprises at least one of a hydrogenated styrene-butadiene block copolymer and a hydrogenated styrene-isoprene block copolymer; (2) The mineral oil includes at least one of silicone oil, paraffin oil, cycloparaffin oil and aromatic hydrocarbon oil; (3) The nylon comprises nylon 6; (4) the maleic anhydride grafted polypropylene comprises at least one of maleic anhydride grafted homopolypropylene, maleic anhydride grafted copolymer polypropylene and maleic anhydride grafted random copolymer polypropylene; (5) The maleic anhydride grafted hydrogenated styrene elastomer comprises at least one of a maleic anhydride grafted hydrogenated styrene-butadiene block copolymer and a maleic anhydride grafted hydrogenated styrene-isoprene block copolymer; (6) The filler includes at least one of white carbon black, wollastonite, calcium carbonate, glass microspheres, talc, kaolin, diatomaceous earth, barium sulfate and mica.

5. The TPE material according to claim 1, characterized in that The invention also comprises the following components in parts by weight: 0.01 to 2 parts of auxiliary agent.

6. The TPE material according to claim 5, characterized in that The auxiliary agent includes at least one of an antioxidant, a light stabilizer and a lubricant.

7. The method for preparing the TPE material according to any one of claims 1 to 6, characterized in that: The following steps are involved: spraying mineral oil into the hydrogenated styrene elastomer while stirring to obtain a premix; The premix is ​​mixed with other raw materials, melt-extruded, granulated, and dried to obtain a TPE material.

8. The method for preparing the TPE material according to claim 7, characterized in that: The temperature of the melt extrusion is 170-250°C.

9. Use of the TPE material according to any one of claims 1 to 6 in battery pack shell encapsulation, explosion-proof tool shell encapsulation or automotive parts encapsulation.

10. A rubber-coated nylon product, characterized in that: It comprises a nylon matrix and a coating material coated on the surface of the nylon matrix, wherein the coating material is the TPE material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Thermoplastic elastomer material for coating glass fiber reinforced nylon and preparation method thereof

    CN109957253A

  • TPE nylon rubber-coated particle material with high fluidity and high binding power and preparation method thereof

    CN112694761A

  • TPE alloy for polyphenyl ether bonding encapsulation as well as preparation method and application of TPE alloy

    CN112759886A

  • High-performance nylon-coated thermoplastic elastomer material as well as preparation method and application thereof

    CN115368703A

  • Nylon rubber-coated TPE (thermoplastic elastomer) composite material as well as preparation method and application thereof

    CN118006133A

Cited By

  • Low-compression permanent deformation nylon-coated thermoplastic elastomer as well as preparation and application thereof

    CN121182222A